Yield of sugar beet with drip irrigation, with Penman’s equation and AquaCrop model - Pinna, Jorge; Rivas, Kevin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
It is necessary to estimate sugar beet yield, because studies with this crop demonstrated than in Peruvian coastal zone, could be a profitable crop. The objective of the present experiment was to know if dry matter yield of sugar beet is related with Penman’s equation, or FAO’s AquaCrop model. Experiment was made in a sandy soil, non-salty, calcareous, very poor in organic matter, with drip irrigation in Peruvian northern coast. Four treatments: two, three, four and five plant rows per irrigation drip line, in a completely random design, with four replications were utilized. Calculated fresh matter weighs with AquaCrop were between 15.5 and 24.5 Mg.ha-1, very much lesser to real ones (between 67.5 and 103.9 Mg.ha-1) hence Aqua Crop model is not effective to estimate yield of sugar beet. It is possible to estimate yield of sugar beet, with Penman’s formula, which varied between 11.40 and 27.96 Mg.ha-1 dry weight, and the real one was between 13.4 and 21.5 Mg.ha-1, with a "Root Mean Square Error" (RMSE) of 3.73.